Immobilization of commercial hydrolytic enzymes on poly (acrylonitrile) nanofibers for anti‐biofilm activity. Issue 4 (27th June 2012) - du Plessis, Danielle Marguerite; Botes, Marelize; Dicks, Leon Milner Theodore; Cloete, Thomas Eugene
Abstract: BACKGROUND: Chemical methods used to control biofilm formation in filtration systems are not always effective. Two commercially available proteases and an amylase were immobilized onto polymer nanofibers that are used in the production of filtration membranes. RESULTS: The enzymes were immobilized onto poly acrylonitrile nanofibers that were chemically activated by imidoesterification to allow the covalent immobilization of enzymes. The immobilized enzymes retained above 80% of the specific activity of the free enzymes. For each of the immobilized enzymes, just below 30% of initial activity was retained after 10 repeated cycles of use. No biofilm formation was observed on nanofibers that were coated with the enzymes, where biofilms formed on non‐coated nanofibers. CONCLUSION: When considering the combined advantages of this effective immobilization process, the robustness of the enzymes used in this study, and the results of this study indicating activity against biofilms, a valuable addition has been made to filtration membrane technology. © 2012 Society of Chemical Industry